If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12p + 14 = -22 Reorder the terms: 14 + -12p = -22 Solving 14 + -12p = -22 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + -12p = -22 + -14 Combine like terms: 14 + -14 = 0 0 + -12p = -22 + -14 -12p = -22 + -14 Combine like terms: -22 + -14 = -36 -12p = -36 Divide each side by '-12'. p = 3 Simplifying p = 3
| -23=-2-a-10+a | | 232.2344=4*3.14r^2 | | 25-25= | | 1.89x+1=0 | | 3x=5(2x-1) | | (2y-1)*(-1)=71 | | 8(y-9)= | | (2x-3)+(3x-1)=(x-2)-(5-6) | | (2x-3)+(3x-1)=(x-2)-(5-6x) | | 6x^2-6x=12x | | 13x=221 | | 10*80.72= | | -4y=1/4 | | -4x+3+5x=9 | | 95-86=26y-35y | | -4=1/4 | | -38=(-6x)-14 | | 3x=4x^2-2x | | 2y+2.2-3.6y-0.6y+3= | | 7h+1= | | 2k=7 | | 6.5x=0.25 | | 6.5x=1/4 | | .2Xa=3 | | 12x+5y+30=0 | | 4X^2+30x-110=0 | | 5x+2y-3x=0 | | 3y+5=-6-22 | | 6x+3(0)=8 | | 19=x-9 | | 13x+18+7x+12=90 | | N+5=5+8 |